IOT-Based Sumo Robot Control Using Blynk Software: Kendali Robot Sumo Berbasis IoT Menggunakan Perangkat Lunak Blynk. - Agus Hayatal Falah; Syamsudduha Syahrorini; Arief Wisaksono; Yoga Eko Prasetyo (Academia Open, 2023)
This study explores the use of IoT technology to enhance communication between Android smartphones and sumo robots, aiming to overcome the limited range of Bluetooth connections. By utilizing the NodeMCU ESP8266 microcontroller, the researchers achieved a connection speed of 4.6 seconds. Furthermore, the step-down circuit test with a 5Vdc power supply and the LiPo 3-cell battery test with a 12.54Vdc power supply yielded positive results. The Bts7960 driver was also successfully tested for clockwise and counterclockwise rotation. Finally, the maneuver test using the Blynk software showcased the robot's ability to respond to four commands—forward, backward, turn left, and turn right—via the IoT system. Highlights: Enhanced communication: Utilizing IoT technology enables improved communication between Android smartphones and sumo robots, expanding the range beyond the limitations of Bluetooth. Efficient connection: The implementation of the NodeMCU ESP8266 microcontroller achieves a speedy connection with a response time of 4.6 seconds, facilitating seamless remote control of the robot. Versatile maneuverability: With the Blynk software and IoT system, the sumo robot can execute four essential commands—forward, backward, turn left, and turn right—providing flexibility and control during operation Keywords: Sumo robot, IoT communication, Android smartphones, NodeMCU ESP8266, Blynk software.